Activity limitation and match load in para-footballers with cerebral palsy: An approach for evidence-based classification - Reina, R.; Iturricastillo, A.; Castillo, D.; Urbán, T.; Yanci, J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Classification is a hot topic in Paralympic sport, making the development of evidence-based and sport-specific classification systems mandatory. However, the development of measurements for exploring the relationships between the athletes' impairment and their activity limitation is a considerable scientific challenge in team Paralympic sport such as 7-side football (ie, CP Football). The aims of this study were 1) to describe the activity limitation and external match load (ML) differences among impairment profiles (FT) in international level footballers with cerebral palsy (CPFP) and 2) to analyze the relationship among the activity limitation and external ML variables. Forty-eight international male CPFP (23 ± 7 y; 174.7 ± 7.2 cm; 69.4 ± 9.2 kg; 22.7 ± 2.6 kg·m-2) participated in this study and were divided according to their impairment profile (FT5/6, FT7, and FT8). Significant differences (P < .05) have been observed among FT profiles in the activity limitation tests (ie, static balance, coordination, vertical jump, horizontal jump, acceleration capacity, and change of direction ability). Additionally, significant differences have been observed among FT profiles in certain ML values (ie, Velmax, High Acc and in Mod and High Dec), where generally, FT8 players reported the best performance values. On the other hand, especially in the FT5/6 and in the FT8 profiles, a large-to-very large significant relationship was observed between the CPFP activity limitation and the ML values. In general, the results of the present study show that players with a lower impairment have less activity limitation and better ML. This study concludes that the potential relationships between the impairments of hypertonia, ataxia, or athetosis and performance in this para-sport might be impairment-specific.